Los medios de comunicación frente a la exploración minera del cantón Balsapamba de la provincia de Bolívar, 2020 - Burgos Montero, Génesis Noemí (2021)
In this project, the problems that exist in the Balsapamaba sector with respect to mining exploration where copper deposits were found by the Chinese company Yankuang Donghuan, through its project in the Telimbela parish, will be made known, who until now They are still exploring in this sector but much deeper, having as inconveniences in these sectors are the protests of the people regarding the non-contamination of the environment, in Balsapamba in a peaceful way since something relevant to natural damage, but in Telimbela there is an opposition group where these transnational companies are not currently allowed to enter. In addition, put the media in context in relation to this issue, and in the way they handle the laws to publicize the rights of citizens and environmental rights to society.